Kenaf fiber/pet yarn reinforced epoxy hybrid polymer composites: morphology, tensile and flammability properties - M. J., Suriani; Zainudin, Hasliana Asyikin; Ilyas, R. A.; Petrů, Michal; Salit, Mohd Sapuan; Ghazali, Che Mohd Ruzaidi; Mustapha, Rohani (MDPI AG, 2021)
The application of natural fibers is rapidly growing in many sectors, such as construction, automobile, and furniture. Kenaf fiber (KF) is a natural fiber that is in demand owing to its eco-friendly and renewable nature. Nowadays, there are various new applications for kenaf, such as in absorbents and building materials. It also has commercial applications, such as in the automotive industry. Magnesium hydroxide (Mg(OH)2) is used as a fire retardant as it is low in cost and has good flame retardancy, while polyester yarn (PET) has high tensile strength. The aim of this study was to determine the horizontal burning rate, tensile strength, and surface morphology of kenaf fiber/PET yarn reinforced epoxy fire retardant composites. The composites were prepared by hybridized epoxy and Mg(OH)2 PET with different amounts of KF content (0%, 20%, 35%, and 50%) using the cold press method. The specimen with 35% KF (epoxy/PET/KF-35) displayed better flammability properties and had the lowest average burning rate of 14.55 mm/min, while epoxy/PET/KF-50 with 50% KF had the highest tensile strength of all the samples. This was due to fewer defects being detected on the surface morphology of epoxy/PET/KF-35 compared to the other samples, which influenced the mechanical properties of the composites.